Implementasi Dakwah Humanis dalam Pelayanan Rohani Pasien di Rumah Sakit - Adzany, Finanda Syakira; Lubis, Yasser Muda (Prodi Manajemen Dakwah Fakultas Dakwah dan Ilmu Komunikasi Universitas PTIQ Jakarta, 2025)
This study explores the implementation of humanist da'wah in spiritual care services at Gunung Jati Regional Hospital Cirebon through the Islamic Spiritual Care Unit (Warois). The research focuses on three main aspects: managerial policy support for humanist da'wah, the role of spiritual counselors in applying an empathetic and non-dogmatic approach, and the supporting and inhibiting factors in its implementation. Using a qualitative case study approach, data were collected through in-depth interviews, observation, and documentation. The findings indicate that humanist da'wah is reflected in empathetic communication, contextual spiritual motivation strategies, and structural support from hospital management. However, challenges remain, including limited personnel, patient resistance, and suboptimal cross-unit coordination. These findings highlight the importance of integrating humanist da'wah into health service systems grounded in spiritual and humanitarian values.